If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10y = -10 Solving 2x + -10y = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10y' to each side of the equation. 2x + -10y + 10y = -10 + 10y Combine like terms: -10y + 10y = 0 2x + 0 = -10 + 10y 2x = -10 + 10y Divide each side by '2'. x = -5 + 5y Simplifying x = -5 + 5y
| 7(x-5)=7x-35 | | 6(x+3)=9-2[x-4(x+1)] | | h=235t-16t^2 | | 62.5= | | 23*y=7385526 | | 2x^2-14=12x | | 6=s/9 | | 9=1.5z | | 3x+2=4p-7 | | a^2+16a+63=0 | | 24z=4z^2 | | y+1=-3/2(x+7) | | 5x/6-5/2=-10/9 | | -6x-6=8 | | x-2/2+x=3x | | -4u-5=11 | | -(3y+1)-(-2y+7)=5 | | -5n(2n-9)=0 | | 9X+12=4X+142 | | 4(3x-8)-11x=1 | | 4q-13=8 | | 4a^4-1025= | | 28-3x=4x+7 | | y+1=-3/2x+5 | | 16.3x+16=12 | | 3/7x=-12 | | 183-2X=34X+14 | | (x+3)(2x-5)+(2x-5)(2x-5)=0 | | x-8.7=3.4 | | (x+3)(2x-5)+(2x-5)2=0 | | -2k=5 | | X^3-3x^2-2x-4=0 |